Proposal to Enhance Fund Support for Low-Income Countries Hit by Public Health Disasters : Proposed Decisions. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2015)
This paper sets forth the proposed decisions and related legal instruments that are needed to implement the transformation of the the Post-Catastrophe Debt Relief Trust (the 'PCDR Trust') into the Catastrophe Containment and Relief Trust (the 'CCR Trust' or 'Trust'), as described in the Proposal to Enhance Fund Support for Low-Income Countries Hit by Public Health Disasters and as presented in an informal session to brief Executive Directors on January 28, 2015. The paper summarizes key aspects of the proposed decisions and related instruments, in particular the new CCR Trust Instrument. The proposed reforms envisage the transformation of the PCDR Trust into the CCR Trust through an amendment of the PCDR Trust Instrument.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet